Does store atmosphere support consumers' desire to shopping? - Dedi Iskamto; Hendrayani Hendrayani; Cornelis Dehotman; Wirdayani Wahab; Siti Syahsudarmi; Asnahwati Asnahwati; Jeli Nata Liyas (Jurnal Pemasaran Kompetitif, 2022)
Store atmosphere is one of the factors owned by the store to attract consumers. Each store has a physical layout that makes it easy and difficult for shoppers to move around in it. Each store has a shop appearance that shapes the atmosphere according to its target market and can attract consumers to buy.This study aims to determine the effect of store atmosphere on consumer decisions in shopping. This study used a quantitative method using SPSS software version 25. Research resultsthat the store atmosphere has a significant effect on consumer decisions in shopping. It was also found that the atmosphere of the store had an influence of 35.6% on consumer decisions in shopping, the remaining 64.4% was influenced by factors not examined in this study.